2017
DOI: 10.3389/fnmol.2017.00270
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Activity and Muscle Contraction Increases PDK1 and PKCβI Phosphorylation in the Presynaptic Membrane of the Neuromuscular Junction

Abstract: Conventional protein kinase C βI (cPKCβI) is a conventional protein kinase C (PKC) isoform directly involved in the regulation of neurotransmitter release in the neuromuscular junction (NMJ). It is located exclusively at the nerve terminal and both synaptic activity and muscle contraction modulate its protein levels and phosphorylation. cPKCβI molecular maturation includes a series of phosphorylation steps, the first of which is mediated by phosphoinositide-dependent kinase 1 (PDK1). Here, we sought to localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…However, before PKCs can be functional, they need to be phosphorylated by PDK1 [77][78][79][80][81]. PDK1 activates multiple signaling pathways and seems to be constitutively active at the NMJ [82]. PDK1-induced PKC phosphorylation is enhanced by synaptic activity but is not directly linked to BDNF/TrkB signaling, which is, contrarily, involved in PKC activation once the isoforms are phosphorylated and mature [36].…”
Section: Bdnf/trkb Signaling In the Nmj Is Regulated By Pre And Postsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before PKCs can be functional, they need to be phosphorylated by PDK1 [77][78][79][80][81]. PDK1 activates multiple signaling pathways and seems to be constitutively active at the NMJ [82]. PDK1-induced PKC phosphorylation is enhanced by synaptic activity but is not directly linked to BDNF/TrkB signaling, which is, contrarily, involved in PKC activation once the isoforms are phosphorylated and mature [36].…”
Section: Bdnf/trkb Signaling In the Nmj Is Regulated By Pre And Postsmentioning
confidence: 99%
“…In skeletal muscles, nerve-induced stimulation, high Ca 2+ concentrations and muscarinic signaling couple PKC to result in neurotransmitter release at the adult NMJ [84,87,88]. In particular, nPKCε maintains ACh release and modulates muscarinic signaling [86], while cPKCβI enhances neurotransmission [82] at the NMJ. Furthermore, evidence supports the importance of neurotrophic signaling via TrkB activity to regulate neuromuscular ACh release at short times and to maintain synaptic function and structural integrity in adult rodent NMJs long term [28,36,42,89,90].…”
Section: Bdnf/trkb Signaling In the Nmj Is Regulated By Pre And Postsmentioning
confidence: 99%
“…Because of these uncertainties, we induced muscle paralysis with μ-CgTx-GIIIB ( Garcia et al, 2013 ; Tomàs et al, 2014 ; Obis et al, 2015 ; Santafé et al, 2015 ; Hurtado et al, 2017a , b ), a specific inhibitor of the sodium channel of the muscle cells which preserves NMJ function ( Garcia et al, 2013 ) and its safety factor. This experimental condition mimics the physiological conditions of this synapse in the living animals except for the absence of the contraction-dependent retrograde influence of the muscle cells ( Besalduch et al, 2011 ; Hurtado et al, 2017a , b ). We observed that 25 μM adenosine reduced (50%) the quantal content of ACh release in agreement with other authors ( Ginsborg and Hirst, 1972 ; Ribeiro and Walker, 1975 ).…”
Section: Adenosine Receptors Role In the Adult Neurotransmissionmentioning
confidence: 99%
“…The AGC protein kinase family includes PDK1, cyclic AMP-dependent protein kinase, PKB/AKT and Ca2 + -activated protein e kinase (22,26). Among the DEGs, the present study found that PDK1, a key upstream gene of AKT, activates ~23 protein kinases in the AGC family, including PKB/AKT, which is a key signaling intermediate involved in growth and l survival (27). Therefore, the levels of these genes were analyzed and it was found that the mRNA and protein expression levels of AKT and PDK1 were significantly increased in the Stra8-GC1 cells compared with those in the Control-GC1 cells.…”
Section: Discussionmentioning
confidence: 49%
“…Based on the above results, the present study further examined the function of AKT-associated genes and pathways. It has (22,26,27). According to associated studies in the literature, AKT can act as a survival factor which balances pro-survival and pro-death signals, including activating genes in the Bcl-2 family and interacting with MAPK gene families, which eventually suppresses escaspases (22,26).…”
Section: Discussionmentioning
confidence: 99%